2016
DOI: 10.1158/1078-0432.ccr-15-1458
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Pathways: AXL, a Membrane Receptor Mediator of Resistance to Therapy

Abstract: AXL is a tyrosine kinase membrane receptor that signals via PI3K, MAPK, and protein kinase C (PKC), among other pathways. AXL has oncogenic potential and interacts with other membrane receptors, depending on their relative abundance and availability. The increased expression of AXL in cancer is often the result of pharmacologic selective pressure to a number of chemotherapies and targeted therapies and acts as a mechanism of acquired drug resistance. This resistance phenotype, frequently accompanied by epithel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
97
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(99 citation statements)
references
References 56 publications
1
97
0
1
Order By: Relevance
“…Ingenuity Regulator Analysis of AD80 direct and indirect targets nominated the tyrosine kinase AXL for further analysis (Table S2). AXL is a member of the TYRO3, AXL, MER (TAM) family of tyrosine kinases, which are emerging as key mediators of resistance to kinase-targeted therapeutics (Elkabets et al, 2015; Scaltriti et al, 2016). Combining the S6K1 inhibitor LY-2779964 with the AXL/TAM kinase inhibitor BMS-777607 elicited substantial cytotoxicity that was selective for PTEN-deficient cells similar to AD80 (Figure 4b, S4a) (Schroeder et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Ingenuity Regulator Analysis of AD80 direct and indirect targets nominated the tyrosine kinase AXL for further analysis (Table S2). AXL is a member of the TYRO3, AXL, MER (TAM) family of tyrosine kinases, which are emerging as key mediators of resistance to kinase-targeted therapeutics (Elkabets et al, 2015; Scaltriti et al, 2016). Combining the S6K1 inhibitor LY-2779964 with the AXL/TAM kinase inhibitor BMS-777607 elicited substantial cytotoxicity that was selective for PTEN-deficient cells similar to AD80 (Figure 4b, S4a) (Schroeder et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…For example, AXL expression was shown to be higher in patients with drug-resistant leukemia and AXL was induced by chemotherapy drugs in leukemia cell lines (34) and by cisplatin in non-small cell lung cancer cells (35). Several studies by our group and others have shown the involvement of AXL in causing EMT-associated resistance to targeted therapy such as EGFR inhibitors and PI3K inhibitors (8) (36). In these studies, inhibition of AXL in the mesenchymal cancer cells re-sensitized these cells to either chemotherapy or targeted therapy (8, 9, 16, 36).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies by our group and others have shown the involvement of AXL in causing EMT-associated resistance to targeted therapy such as EGFR inhibitors and PI3K inhibitors (8) (36). In these studies, inhibition of AXL in the mesenchymal cancer cells re-sensitized these cells to either chemotherapy or targeted therapy (8, 9, 16, 36). Further, the relationship between EMT and DNA repair pathways has been recently observed in several systems.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that the AXL RNA expression level significantly increased in crizotinib‐resistant HCC78R cells. AXL is thought to play a role in acquired resistance to oncoprotein inhibitors, but its role regarding crizotinib resistance has not yet been reported. We examined the effects of 2 clinically relevant AXL inhibitors in HCC78R cells.…”
Section: Discussionmentioning
confidence: 99%